General Solution and Generalized Hyers-Ulam Stability of n-dimensional Cubic Functional Equation in Various Normed Space: Direct and Fixed Point Methods
In this paper, the authors investigate the general solution in vectors space and generalized Hyers-Ulam Stability of n-dimensional Cubic functional Equation f(^n_i=1x_i )+^n_j=1f(-x_j+_i=1;i eq jx_i )=(n-5)_ 1≤ i<j≤ k≤ n f(x_i+x_j+x_k ) +(-n^2+8n-11)_i=1;i eq jf(x_i+x_j)-^n_j=1f(2x_j ) +12(n^3-10n^2+23n+2)^n_i=1f(x_i ) with n>5, and n is a positive integer using FNS,RNS,IFNS and FELBIN'S type spaces, using direct and fixed point methods. , number=1 - D, journal=International Journal of Mathematics And its Applications, author=S. Murthy and M. Arunkumar and V. Govindan, year=2016, month=Mar., pages=81–109